PENGARUH KOMPENSASI, PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Ariesa, Yeni; Kamal, Jakson; Fransisca, Fransisca; Gunawan, Gunawan; Emmanuel, Alexandrio (Graduate Program Magister Manajemen Pendidikan, 2020)
This research tested the effect of compensation, supervision and work discipline on employee performance at PT Jaya Mandiri Bangunan. The performance of PT Jaya Mandiri Bangunan's employees has decreased due to unsatisfactory compensation, oversight that is still not optimal and work discipline that has not been good. The population and sample in this study amounted to 68 employees of PT Jaya Mandiri Bangunan. The research method uses multiple linear regression analysis techniques. The results of calculation of hypothesis testing indicate that partially compensation, supervision and work discipline have a positive and significant effect on employee performance at PT Jaya Mandiri Bangunan. Simultaneously compensation, supervision and work discipline have a positive and significant effect on employee performance at PT Jaya Mandiri Bangunan.